Not guilty by reason of insanity: a critical examination of Section 84 of the Brunei Penal Code - Masum, Ahmad; Ahmad, Muhamad Hassan; Mohamed Nafees, Seeni Mohamed (Sweet & Maxwell Malaysia, 2020)
It has been ethically, legally and socially accepted that a person who is suffering from insanity cannot and should not be criminally responsible for his actions or inactions. A mentally ill person is not punished for his crime, as he is devoid of free will, intelligence and knowledge of the act. The defence of insanity provides protection to persons with insanity. It plays a vital role in giving protection from criminal liability to such persons who cannot understand the nature of their acts due to their insanity. The basis of the defence of insanity lies in the maxim Actus reus non facit reum, nisi mens sit rea which means that no man can be proved guilty unless he has a guilty mind. Whenever an insane person commits a crime due to the effect of his insanity, he does not have a guilty mind to understand that what he is doing is prohibited by law. The Brunei criminal law system has laid down the defence of insanity under s 84 of the Brunei Penal Code (Cap 22). This paper critically examines the law relating to the defence of insanity under the Bruneian criminal law system by making reference to the Penal Code. The methodology adopted in this paper is legal library-based research focusing mainly on primary and secondary legal sources. The paper concludes that the extent to which the defence of insanity may hold is not certain. In Brunei, judges are not readily moved by such defence neither is the society. In addition, legal scholars and jurists are greatly limited in the knowledge of psychology behind abnormality and the behavioural altitudes that could pass the definition of insanity. The paper recommends that there is a need to return to a more common sense and humane interpretation of legal insanity by paying closer attention to the severity of the emotional disturbance of the individual committing the disturbed and illogical act.